Pengaruh Konsentrasi NaOH yang Berbeda Terhadaap Mutu Agar Rumput Laut Gracilaria verrucosa - Kusuma, Wakhid Indra; Santosa, Gunawan Widi; Pramesti, Rini (977-2407769)
ponds in Indonesian. Agar from G. verrucosa is widely used in the food industry, one of which is used as a thickener or stabilizer of food. However, a good quality of agar with high durability needs developed. The purpose of this study with the addition of NaOH before extracted is to determine the effect of different concentrations of NaOH on the agar quality of seaweed G. verrucosa. This study was conducted from July 30 until August 16, 2012 in Plant Tissue Culture Laboratory, Faculty of Science and Mathematics - University of Diponegoro. Sampling was conducted on July 21, 2012. G. verrucosa was obtained from local ponds Tambak Harjo, Krapyak, District of West Semarang - Semarang. The method used was laboratory experimental methods with completely randomized design (CRD) to determine differences in the concentration of NaOH. The results showed that the effect of the concentration of NaOH affected the gel strength, sulphate content, ash content, moisture content, and yield on agar G. verrucosa (p Ë‚ 0,05). The higher the concentration of NaOH the higher gel strength, ash content, water content, and yield, but lowering sulphate levels. The best results obtained in the treatment with NaOH solution concentration of 6 %.